Novel insights from NMR spectroscopy into seasonal changes in the composition of dissolved organic matter exported to the Bering Sea by the Yukon River. (15th May 2016) - Cao, Xiaoyan; Aiken, George R.; Spencer, Robert G.M.; Butler, Kenna; Mao, Jingdong; Schmidt-Rohr, Klaus
Abstract: Seasonal (spring freshet, summer–autumn, and winter) variability in the chemical composition of dissolved organic matter (DOM) from the Yukon River was determined using advanced one- and two-dimensional (2D) solid-state NMR spectroscopy, coupled with isotopic measurements and UV–visible spectroscopy. Analyses were performed on two major DOM fractions, the hydrophobic organic acid (HPOA) and transphilic organic acid (TPIA) fractions obtained using XAD resins. Together these two fractions comprised 64–74% of the total DOM. Carboxyl-rich alicyclic molecules (CRAM) accounted for the majority of carbon atoms in the HPOA (63–77%) and TPIA (54–78%) samples, and more so in winter and summer than in spring samples. 2D and selective NMR data revealed association of abundant nonprotonated O-alkyl and quaternary alkyl C (OCnp, OCnp O and Cq, 13–17% of HPOA and 15–20% of TPIA) and isolated O–CH structures with CRAM, which were not recognized in previous studies. Spectral editing and 2D NMR allowed for the discrimination of carbohydrate-like O-alkyl C from non-carbohydrate O-alkyl C. Whereas two spring freshet TPIA samples contained carbohydrate clusters such as carboxylated carbohydrates (16% and 26%), TPIA samples from other seasons or HPOA samples mostly had small amounts (<8%) of sugar rings dispersed in a nonpolar alkyl environment. Though nonprotonated aromatic C represented the largest fraction of aromatic C in all HPOA/TPIA isolates, only a small fraction (∼5% in HPOA and 3% in TPIA) was possibly associated with dissolved black carbon. Our results imply a relatively stable portion of DOM exported by the Yukon River across different seasons, due to the predominance of CRAM and their associated nonprotonated C–O and O–C–O structures, and elevated reactivity (bio- and photo-lability) of spring DOM due to the presence of terrestrial inputs enriched in carbohydrates and aromatic structures.